2014
DOI: 10.3390/ijms15057124
|View full text |Cite
|
Sign up to set email alerts
|

SREBP-1 Has a Prognostic Role and Contributes to Invasion and Metastasis in Human Hepatocellular Carcinoma

Abstract: Sterol regulatory element-binding protein 1 (SREBP-1) is a well-known nuclear transcription factor involved in lipid synthesis. Recent studies have focused on its functions in tumor cell proliferation and apoptosis, but its role in cell migration and invasion, especially in hepatocellular carcinoma (HCC), is still unclear. In this study, we found that the expression of SREBP-1 in HCC tissues was significantly higher than those in matched tumor-adjacent tissues (p < 0.05). SREBP-1 was expressed at significantly… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

1
88
0

Year Published

2014
2014
2020
2020

Publication Types

Select...
9

Relationship

0
9

Authors

Journals

citations
Cited by 107 publications
(89 citation statements)
references
References 26 publications
(27 reference statements)
1
88
0
Order By: Relevance
“…Transwell assays were done in 6 well plates with Transwell inserts equipped with 8-μm pores (Nalge Nunc International Corp, Naperville, IL, USA) coated with Matrigel at 1:6 dilution (Becton Dickinson Labware, Bedford, MA, USA) as previously described [26]. …”
Section: Methodsmentioning
confidence: 99%
“…Transwell assays were done in 6 well plates with Transwell inserts equipped with 8-μm pores (Nalge Nunc International Corp, Naperville, IL, USA) coated with Matrigel at 1:6 dilution (Becton Dickinson Labware, Bedford, MA, USA) as previously described [26]. …”
Section: Methodsmentioning
confidence: 99%
“…Recent studies have demonstrated that both lipid synthesis and uptake are significantly elevated in malignancies to support tumor growth [1014]. SREBP-1 is highly expressed in glioblastoma (GBM) [60, 61], the most deadly brain tumor [62], and in prostate [63], endometrial [64], breast cancers [65, 66], hepatocellular carcinoma (HCC) [67], ovarian cancer [68], and pancreatic cancer (Table 1) [69]. The function of SREBP-1 has been investigated in multiple cancer cell lines including colon [70], lung [71] and pancreatic cancer cell lines [72].…”
Section: Activation Of Scap/srebps In Cancermentioning
confidence: 99%
“…Compared with adjacent normal tissues, SREBP‐1 expression is high in HCC tissues. The positive expression of SREBP‐1 is correlated with poor survival of HCC patients (Li et al ., 2014). SREBP transcriptional activity is generally low in normal and nonproliferating cells, which typically import lipids from the extracellular environment.…”
Section: Introductionmentioning
confidence: 99%